Galectin-9 expression defines exhausted T cells and impaired cytotoxic NK cells in patients with virus-associated solid tumors. Issue 2 (12th December 2020) - Okoye, Isobel; Xu, Lai; Motamedi, Melika; Parashar, Pallavi; Walker, John W; Elahi, Shokrollah
Abstract : Background: We have previously reported that the upregulation of galectin-9 (Gal-9) on CD4 + and CD8 + T cells in HIV patients was associated with impaired T cell effector functions. Gal-9 is a ligand for T cell immunoglobulin and mucin domain-3, and its expression on T cells in cancer has not been investigated. Therefore, we aimed to investigate the expression level and effects of Gal-9 on T cell functions in patients with virus-associated solid tumors (VASTs). Methods: 40 patients with VASTs through a non-randomized and biomarker-driven phase II LATENT trial were investigated. Peripheral blood mononuclear cells and tumor biopsies were obtained and subjected to immunophenotyping. In this trial, the effects of oral valproate and avelumab (anti-PD-L1) was investigated in regards to the expression of Gal-9 on T cells. Results: We report the upregulation of Gal-9 expression by peripheral and tumor-infiltrating CD4 + and CD8 + T lymphocytes in patients with VASTs. Our results indicate that Gal-9 expression is associated with dysfunctional T cell effector functions in the periphery and tumor microenvironment (TME). Coexpression of Gal-9 with PD-1 or T cell immunoglobulin and ITIM domain (TIGIT) exhibited a synergistic inhibitory effect and enhanced an exhausted T cell phenotype. Besides, responding patients to treatment had lower Gal-9 mRNA expression in the TME. Translocation of Gal-9 from the cytosol to the cell membrane of T cells following stimulation suggests persistent T cell receptor (TCR) stimulation as a potential contributing factor in Gal-9 upregulation in patients with VASTs. Moreover, partial colocalization of Gal-9 with CD3 on T cells likely impacts the initiation of signal transduction via TCR as shown by the upregulation of ZAP70 in Gal-9+ T cells. Also, we found an expansion of Gal-9+ but not TIGIT+ NK cells in patients with VASTs; however, dichotomous to TIGIT+ NK cells, Gal-9+ NK cells exhibited impaired cytotoxic molecules but higher Interferon gamma (IFN-γ) expression. Conclusion: Our data indicate that higher Gal-9-expressing CD8 + T cells were associated with poor prognosis following immunotherapy with anti-Programmed death-ligand 1 (PD-L1) (avelumab) in our patients' cohort. Therefore, for the very first time to our knowledge, we report Gal-9 as a novel marker of T cell exhaustion and the potential target of immunotherapy in patients with VASTs.